Effects of Three Kinds of Kombucha on the Surface of Composite Resin for Dental Restoration - Ye-Won Song; Sun-Young Park; Ye-Eun Kim; Hye-Won Lee; Jung-Yeon Jae; Hyeon-Ji Shim; Hee-Jung Lim; Im-Hee Jung; Do-Seon Lim (치위생과학회지)
Background: This study aimed to evaluate the effects of kombucha on the surface of composite resins and to examine the degradation-inhibiting effect of adding calcium to kombucha. Methods: Six experimental groups were established, with three types of liquid kombucha: one with 3% added calcium, carbonated water as a positive control, and mineral water as a negative control. The pH and titratable acidity values of the experimental groups were measured. The samples were filled with condensed composite resin and placed in the experimental drinks for 5, 15, 30, and 60 minutes. The Vickers microhardness of the surface was measured before and after immersion, and the changes were compared. Results: The pH values of the experimental group were I’m alive (2.87±0.02), Hollys (2.95±0.01), Ediya (2.99±0.01), I’m alive +3% Ca (4.09±0.01), carbonated water (4.66±0.01), and mineral water (7.67±0.02). I’m alive (–12.35) showed the largest reduction in surface hardness, followed by Hollys (–9.78), carbonated water (–7.97), I’m alive +3% Ca (–7.82), Ediya (–7.60), and mineral water (–1.56). In the Vickers microhardness measurements, all experimental groups, except for the mineral water group, showed significant differences (p＜0.05). The scanning electron microscope results showed that the experimental group and positive control had rough surfaces and micropores. Conclusion: The surface hardness was significantly reduced in all experimental groups except for water. In particular, in the case of kombucha with low pH, the reduction rate increased, weakening the physical properties of the material. In addition, the reduction rate of surface hardness was lower in kombucha with added calcium, and it is believed that drinking kombucha containing calcium can minimize the erosion of dental materials.